The influence of performance objectives on the implementation of lean manufacturing practices: An analysis based on strategic groups - Hamilton Pozo; Orlando Roque da Silva; Takeshy Tachizawa (Cogent Business & Management, 2017)
This paper explores how the choices about, and implementation of, lean production practices are influenced by performance goals prioritized by firms in the context of operations strategy. We analyzed a set of 56 companies (divided into four strategic groups) in the auto parts industry in the cities of Campinas and Jundiaí areas (Brazil). These groups of firms that adopt similar strategic orientations were used to investigate the relationship between the implementation of lean manufacturing practices and the choice of performance objectives. The results suggest that taking into consideration strategic groups can improve the understanding of how performance objectives define lean manufacturing practices adopted by manufacturing companies.
Keywords: 650